Decent work for all its meaning and content, social dimensions and SADC policy perspectives - Setlojoane, Pheta John (Institute of Development and Labour Law, 2014)
The world is undergoing rapid changes some of which dent both the social and economic development. The world of work gets affected by these changes. Society faces risks that ultimately leave many of its members poor and destitute. At the end of the day society looks up to the government to provide solution for these problems. It is at this juncture that the state has to formulate policies that can best deal with this kind of issues. Social protection becomes very important in an attempt to ward off the harmful effects of the risks society faces. However both experience and research would have one believe that finding social protection that is comprehensive for the benefit of the entire society is an uphill battle especially in developing or low in some economies. The SADC region is not immune to this predicament as it is considered one of the poorest in the world. Nevertheless, this does not mean that the region is succumbing to this challenge as it continues to find possible ways out. Its initiatives have been to include in its policy formulation the measures that are advocated by the ILO in order to strengthen their regional policies especially in the labour law context. For this reason the importance of the ILO in the regional policy promotion and development cannot be overemphasized. The idea of "borrowing and bending" still continues in the region. Not only is this important within the labour law context, but in other disciplines. The ILO introduced, in one of its recent reports, the concept of decent work for all. The cardinal issue is the importance and relevance of this concept and its content in fostering social protection and labour issues in the SADC region. This question is the fulcrum upon which the discussion in this study is based